BTN3A2 Expression Is Connected With Favorable Prognosis and High Infiltrating Immune in Lung Adenocarcinoma - Lin, Yuansheng; Zhou, Hao; Li, Shengjun (Frontiers in Genetics, 2022)
Background: butyrophilin subfamily 3 member A2 (BTN3A2) as a important mediator in immune activation, its reported to be linked to many cancers progress. However, the relation with infiltrating immune and prognosis of BTN3A2 in Lung adenocarcinoma are not clear. Methods: In our study, we checked the mRNA expression and protein expression profile of BTN3A2 in Lung adenocarcinoma (LUAD) and its relation to clinical outcomes using TIMER, UALCAN database. Besides, we analyzed the survival of BTN3A2 in LUAD by Kaplan-Meier Plotter and PrognoScan database. Moreover, we analyzed Gene Set Enrichment Analysis (GSEA) of the BTN3A2. Next, we explored the relation of BTN3A2 expression with the immune infiltration by TIMER. At last, In order to enrich the regulatory mechanism of BTN3A2, we used miRarbase, starbase and miRDB dadabase to look for miRNAs targets of BTN3A2. Results: the mRNA along with protein expression of BTN3A2 in the LUAD group was lower in contrast with that in the normal group. Besides, high BTN3A2 expression was connected with good first progression (FP) and overall survival (OS) in LUAD. Then, the GSEA analysis demonstrated that T cell receptor signaling cascade, B cell receptor signaling cascade, natural killer cell mediated cytotoxicity, immune receptor activity, immunological synapse, T cell activation were enriched differentially in BTN3A2 high expression phenotype of LUAD. Moreover, BTN3A2 expression is remarkable positively correlation with invading levels of tumor purity, B cells, neutrophil, CD4+ T cells, dendritic cells, macrophages, and CD8+ T cells in LUAD, and B cells and dendritic cells were linked with good prognosis of LUAD. To further enrich the possible regulatory mechanisms of BTN3A2, we analyzed the miRNA targets. The results showed that hsa-miR-17-5p may be miRNA targets of BTN3A2. Conclusion: Taking together, we provide evidence of BTN3A2 as possible prognosis biomarkers of LUAD. Besides, high BTN3A2 expression in LUAD may influence prognosis because of immune invasion. Moreover, our findings provide a potential mechanism that hsa-miR-17-5p may be miRNA targets of BTN3A2.